Implementation Models and Examples of Health Policy in Indonesia - Nasution, Irfan Sazali; Br. Ginting, Hutri Agustina; Br Purba, Saskia Khairunnisa; Hutagalung, Nuraisyah Dera Marsella; Nasution, Fiola Syifa Azura; Kesuma, Aldimas Maulana; Gurusinga, Rizka Azura Efsa; Lubis, Selvia; Rizky, Dinda Julia; Sitorus, Rezki Alya Mawaddah (Universitas Ibn Khaldun Bogor, 2024)
Indonesia's health policy continues to develop in line with changes in community needs and the global situation (Ministry of Health, 2020). However, the implementation of health policies often faces various challenges. Therefore, this research was conducted with the aim of analyzing examples of health policy implementation in Indonesia, including the problems. The research method used in this research is a qualitative descriptive method, namely collecting data from various secondary sources including journals, government reports and other official articles. The terms used in the literature review as a source for writing this journal are implementation, policy, and health. The results of this research show that the implementation of health policy in Indonesia faces various challenges, suchas limited resources, lack of coordination between stakeholders, and cultural barriers, as well as achieving optimal results varies. This also shows that improvements are needed in certain aspects.